(untitled) (Journal of actual problems of jurisprudence, 2018)
The article describes and analyzes the problems of professional ethics of lawyer as a factor of moral education of personality and the formation of respect to the law and rights.Nowadays the research of professional ethics of lawyer and professional training takes very important place.Everyday lawyers face with people’s problems and they have to solve them competently, efficiently and intelligently because the trust of society to the State manifested through these relationships. Key words: professional ethics of lawyer, professional training, moral principles, professional code of ethics.